2018
DOI: 10.15507/0236-2910.028.201801.120-136
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Forecasting Performance Indicators for Educational Activites of Higher Educational Institution

Abstract: Аллахвердиев Сурхай Рагим оглы-академик Российской Академии Естествознания, профессор кафедры лесной индустрии, Бартынский государственный университет, профессор кафедры экологии и природопользования, ФГБОУ ВО «Московский педагогический государственный университет», доктор биологических наук, профессор (Бартын, Турция) Булгаков Алексей Григорьевич-профессор Института строительного дела, Дрезденский технический университет, доктор технических наук, профессор (Дрезден, Германия) Димитров Валерий Петрович-заведую… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The problem of models, algorithms and software development for forecasting the main indicators of universities' efficiency has been considered in a number of scientific papers [1,2]. They have shown that the information systems (both commercial and proprietary) used in most universities, as a rule, do not allow to calculate all the forecast values of efficiency indicators.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of models, algorithms and software development for forecasting the main indicators of universities' efficiency has been considered in a number of scientific papers [1,2]. They have shown that the information systems (both commercial and proprietary) used in most universities, as a rule, do not allow to calculate all the forecast values of efficiency indicators.…”
Section: Introductionmentioning
confidence: 99%